Incidence and Risk Factors for Unplanned Return to the Operating Room Following Primary Definitive Fusion for Pediatric Spinal Deformity: A Multicenter Study with Minimum 2-year Follow-Up. Issue 8 (15th April 2021) - Taniguchi, Yuki; Ohara, Tetsuya; Suzuki, Satoshi; Watanabe, Kota; Suzuki, Teppei; Uno, Koki; Yamaguchi, Toru; Yanagida, Haruhisa; Nakayama, Keita; Kotani, Toshiaki; Watanabe, Kei; Hirano, Toru; et al.
Abstract : Study Design: A retrospective multicenter cohort study. Objective: The aim of this study was to identify the incidence and risk factors for UPROR within minimum 2-year follow-up in primary definitive fusion for pediatric spinal deformity. Summary of Background Data: Several previous reports have elucidated the incidence of complications after pediatric scoliosis surgery; however, there has been no study that described the incidence and risk factors for unplanned return to the operating room (UPROR) with long-term follow-up in surgery for pediatric scoliosis with every etiology. Methods: We retrospectively extracted data of patients aged <19 years, from 14 institutes in Japan, who underwent primary definitive fusion surgery for spinal deformity between January 1, 2015 and December 31, 2017. The primary outcomes were the incidence of UPROR within the minimum 2-year follow-up period for any reason. Univariate and multivariate logistical analyses were conducted to identify potential risk factors associated with UPROR. Results: We identified 1417 eligible patients (287 males and 1130 females) with a mean age of 13.9 years. UPROR for any reason within minimum 2-year follow-up was identified in 68 patients (4.8%). The most frequent cause for UPROR was implant failure found in 29 patients, followed by surgical site infection in 14 patients, junctional problems in 10 patients, and neurological complications in six patients. The multivariate logistic regression analysis revealed that a diagnosis of kyphosis (odds ratio [OR], 2.65; 95% confidence interval [CI] 1.16–6.04), etiology of congenital or structural type (OR 2.21; 95% CI 1.08–4.53), etiology of syndromic type (OR 2.67; 95% CI 1.27–5.64), and increased operation time of ≥300 minutes (OR 1.81; 95% CI 1.07–3.07) were the risk factors for the incidence of UPROR. Conclusion: The present multicenter study identified for the first time the incidence and risk factors for UPROR with minimum 2-year follow-up after primary definitive fusion surgery for pediatric spinal deformity with every etiology. Level of Evidence: 3 Abstract : Unplanned return to operating room (UPROR) following primary fusion for pediatric spinal deformity within minimum 2-year follow-up was identified in 4.8% of patients. The risk factors for UPROR were diagnosis of kyphosis, etiology of congenital or structural type, etiology of syndromic type, and increased operation time of ≥300 minutes.